Fractal Analysis in Problems of the Applied Physics - Chernogor, L. F.; Lazorenko, O. V.; Onishchenko, A. A. (Taras Shevchenko National University of Kyiv, 2022)
For the researchers, a review of the existing mono-fractal analysis methods applied in different branches of modern applied physics is proposed. For each mono-fractal analysis method, some actual references allowing to study the method and to develope corresponding numerical realization are given